2017
DOI: 10.5539/ijbm.v12n3p170
|View full text |Cite
|
Sign up to set email alerts
|

The Opinion of Auditors towards the Importance and Knowledge of Information Technology in Kuwait

Abstract: The current study attempts to explore the attitudes of the auditors towards the level of knowledge of Information Technology (IT) and its importance in Kuwait. To achieve these objectives, structure questionnaires were distributed among these auditors. The analysis covers 5 technology categories namely General Office Automation (GOA), Audit Automation (AA), Accounting Firm Office Automation (AFOA), E-Commerce Technologies (ECT) and System Design and Implementation (SDI).It is found that the view of auditors to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…However, auditors still prefer to apply traditional audit procedures when forming an audit opinion (Ahmi & Kent, 2013;Bierstaker et al, 2014;Siew et al, 2020). Previous studies reported a low level of IT competency among auditors (Al-Duwaila & Abdullah, 2017;Greenstein & McKee, 2004;Strong & Portz, 2015). Particularly in Yemen, external auditors face the deficiency of knowledge and skills related to IT audit processes, contributing to their inefficiency in using technology effectively (Al-Ansi, 2015;Al-Sorihi, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, auditors still prefer to apply traditional audit procedures when forming an audit opinion (Ahmi & Kent, 2013;Bierstaker et al, 2014;Siew et al, 2020). Previous studies reported a low level of IT competency among auditors (Al-Duwaila & Abdullah, 2017;Greenstein & McKee, 2004;Strong & Portz, 2015). Particularly in Yemen, external auditors face the deficiency of knowledge and skills related to IT audit processes, contributing to their inefficiency in using technology effectively (Al-Ansi, 2015;Al-Sorihi, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous IT competency studies on accounting practitioners have focused on issues related to their level of IT knowledge, the importance of IT skills, the identification of IT skills requirements, the alignment of IT knowledge and IT importance, and the integration of IT competency into accounting curricula (Al-Duwaila & Abdullah, 2017;Bahador & Haider, 2017;Greenstein & McKee, 2004;Spraakman et al, 2015). However, only a few studies have examined the factors that impact the IT competency of accountants (Alkhaffaf et al, 2017(Alkhaffaf et al, , 2018Bahador & Haider, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…FromdifferentperspectivesofITcompetency,previousstudieshavefocusedonissuesrelated todeterminingtherequirementofITskillsforaccountingpractitioners,theimportanceofITskills foraccountingpractitioners,theintegrationofITcompetencyintotheaccountingcurriculum,the levelofITknowledgeamongaccountingpractitioners,andthealignmentbetweenITknowledge and IT importance among accounting practitioners (Al-Duwaila & Abdullah, 2017;Bahador et al,2018;Greenstein&McKee,2004;Spraakmanetal.,2015).However,onlyafewstudieshave examinedthefactorsthatinfluencedtheITcompetencyofaccountants (Alkhaffaf,Idris,Abdullah, &Al-Aidaros,2017Bahador,2014).Forexample, Bahador(2014)conductedaqualitative studytodevelopanITcompetencyframeworkforprofessionalaccountantsandproposedseveral skillsdevelopmentfactorsthatmightinfluenceITcompetency.Amongthosefactorswereaccounting education,professionalaccountingbodies,andself-directedlearning(SDL).MotivatedbyBahador's study, Alkhaffafet al(2017Alkhaffafet al( ,2018studieddifferentfactorsthatinfluencedITcompetencies,such asachievement,motivation,andgoalsetting.Alkhaffaf'studyfocusedonITcompetenciesamong accountantsworkinginthepublicsectorinIraqanddidnotconcentrateonspecificgroups,such asexternalauditors,andrecommendedmoreresearchtobeundertakentoidentifythefactorsthat influenceITcompetencyfromdifferentcontextsandperspectives.Therefore,thisstudyaimstofill thisgapbyexaminingtheinfluenceofaccountingeducation,professionalaccountingbodies,and SDLontheITcompetencyofexternalauditorsinYemen.…”
Section: Introductionmentioning
confidence: 99%